Pengaruh Metabolit Sekunder Trichoderma spp. dan Fungisida Nabati untuk Mengendalikan Penyakit VSD pada Tanaman Kakao - Rita Harni; Widi Amaria; Anis Herliyati Mahsunah; Irwan Lakani (Jurnal Tanaman Industri dan Penyegar, 2019)
Vascular streak dieback (VSD) caused by Ceratobasidium theobromae is a major disease in cacao which results in yield losses up to 45%. Controlling VSD using secondary metabolites and botanical fungicide is expected to reduce disease attacks because secondary metabolites contain antibiotics, enzymes, and toxins that can control the disease and botanical fungicide that are antifungal. The research aimed to determine the effect of Trichoderma spp. secondary metabolites and botanical fungicide to control VSD in cacao. The research was conducted in the Integrated Laboratory, IIBCRI, Sukabumi, Biotechnology Laboratory, BPPT, Serpong and farmer gardens in Rahmat Village, Palolo District, Sigi Regency, Central Sulawesi, from March to December 2017. The research used a randomized block design of 7 treatments with 3 replications; each replication consists of 10 plants. The treatments were: (1) Trichoderma virens LP1, (2) T. amazonicum LP3, (3) botanical fungicide, (4) T. virens LP1 + botanical fungicide, (5) T. amazonicum LP3 + botanical fungicide, (6) chemical fungicide (for comparison), (7) control (without application). Variables observed were the symptoms of the attack, severity and disease progression, and production. The results showed that Trichoderma spp. secondary metabolites suppress VSD disease severity and increase cacao production up to 33.97%–61.34%, either in a single form or in combination with botanical fungicide. T. virens LP1 secondary metabolite showed the highest suppression of VSD disease (54.18%), followed by the combination of T. virens LP1 + botanical fungicide (47.64%), better than chemical fungicide (30.89%). Thus, Trichoderma spp. secondary metabolites can be used as a VSD control technology.